The Influence of Content Marketing, Online Customer Reviews, and Cash on Delivery on Consumer Purchasing Decisions at Tiktok Shop in Batam City - Simorangkir, Melani; Hikmah, Hikmah (Universitas Batanghari, 2024)
The purpose of this research is to find out how Tiktok Shop in Batam City, Indonesia uses content marketing, online customer review, and cash on delivery to influence customers' choices to buy The Originote items. The data for this research was gathered using a Google Form questionnaire. People that use the TikTok app and buy the original items will fill out the survey, which uses a Likert scale for measuring. 204 people participated in this research. The research used a causality design to examine the relationship between the variables that were chosen for analysis. With SPSS version 25, we were able to determine the coefficient of determination. Content marketing, online customer reviews, and cash on delivery impact purchase choices by 48.5%, according to the study and data analysis that was carried out.